E-Science and Web 2.0 in Higher Education (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
There are many definitions of Web 2.0 which, however, do not exclude each other. Tim O’Reilly and Dale Dougherty first used the term in 2004 when they came up with an idea of conference about Web technology development. Today, we have different numbers of Web 2.0 tools on the Internet with different purpose, and many of them are implemented in education. The education system is subject to a number of changes to ensure the quality of the studies. Thus, the introduction of new technology that allows better communication, research and access to lectures alone creates a better learning environment and easier to study. The presence of new technologies provides an entirely new approach to the education system. In this paper we will present a few Web 2.0 tools and also how they affect in Croatian education on polytechnics. By polling of the students we want to determine how much they are familiar with web technologies in a way to examine their current habits and how they should be altered to accept new technologies in education and educational systems. With results of the survey will be shown the impact of technology at polytechnics in Croatia and in the discussion we will to explain why this is so because we assume that Web technology underutilized in higher education.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.